2017
DOI: 10.4236/as.2017.87049
|View full text |Cite
|
Sign up to set email alerts
|

US Resident Perceptions of Dairy Cattle Management Practices

Abstract: As public perception continues to shape the dairy industry, an understanding of consumer views and purchasing behaviors is critically important. The objectives of this paper are to: 1) summarize consumer perceptions or views of 12 common dairy cattle management practices (humane methods of slaughter, humane transportation, increased pen stall or size, access to pasture, feeding of a GMO-free diet, feeding of an organic diet, feeding of a diet the animal would naturally consume, ability to interact with other a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 13 publications
0
13
0
Order By: Relevance
“…Consumers’ awareness, willingness and dietary change regarding animals and animal agriculture have been studied with participants from several countries in North and South America (Canada [ 86 , 87 , 88 ], U.S. [ 86 , 87 , 89 , 90 , 91 , 92 , 93 , 94 , 95 , 96 , 97 , 98 , 99 , 100 , 101 , 102 , 103 , 104 , 105 ], Mexico [ 106 , 107 ], Argentina [ 108 ], Bolivia [ 108 ], Brazil [ 71 , 72 , 109 , 110 , 111 , 112 , 113 , 114 , 115 ], Chile [ 108 , 116 ], Colombia [ 108 ], Ecuador [ 108 ], Peru [ 108 ]), Western and Eastern Europe (Belgium [ 109 , 117 , 118 , 119 , 120 ], Denmark [ 117 ], Finland [ 121 , 122 , 123 ], France [ 115 , 119 , 124 ], Germany [ 117 ...…”
Section: Resultsmentioning
confidence: 99%
“…Consumers’ awareness, willingness and dietary change regarding animals and animal agriculture have been studied with participants from several countries in North and South America (Canada [ 86 , 87 , 88 ], U.S. [ 86 , 87 , 89 , 90 , 91 , 92 , 93 , 94 , 95 , 96 , 97 , 98 , 99 , 100 , 101 , 102 , 103 , 104 , 105 ], Mexico [ 106 , 107 ], Argentina [ 108 ], Bolivia [ 108 ], Brazil [ 71 , 72 , 109 , 110 , 111 , 112 , 113 , 114 , 115 ], Chile [ 108 , 116 ], Colombia [ 108 ], Ecuador [ 108 ], Peru [ 108 ]), Western and Eastern Europe (Belgium [ 109 , 117 , 118 , 119 , 120 ], Denmark [ 117 ], Finland [ 121 , 122 , 123 ], France [ 115 , 119 , 124 ], Germany [ 117 ...…”
Section: Resultsmentioning
confidence: 99%
“…Previous work has shown that many US citizens (63%) are concerned about the welfare of dairy cattle [37]. Moreover a number of studies have examined public support for specific dairy management practices such as tail docking [3,38], cow-calf separation [39,40], dehorning [3,41] and provision of pasture access [3,42]. Most of these studies have found a substantial gap between public support and current industry practice.…”
Section: 0 Discussionmentioning
confidence: 99%
“…The emphasis on restrictive housing systems seems to reflect widespread public sentiment that animals lacking the opportunity to move freely and express normal, social behaviors have reduced levels of welfare [2]. In one recent survey of US citizens the ability of animals to interact socially was perceived as the most important factor for ensuring the welfare of dairy cattle [3]. Collectively there is a growing body of evidence that restrictive housing is a source of public controversy.…”
Section: 0 Introductionmentioning
confidence: 99%
“…Global production of milk has doubled over the past 50 yr (Roser and Ritchie, 2019), yet dairy farming in high-income countries faces scrutiny over its practices, especially those believed to affect the welfare of the cow (Olynk Widmar et al, 2017;Placzek et al, 2021). A particular concern is the impact of different living environments, chiefly how long the cow spends inside housing or out at pasture (Ellis et al, 2009), which is usually a component of the dairy farming system adopted.…”
Section: A Growing Disconnectmentioning
confidence: 99%